A new polyploid species of Mecardonia (Gratioleae, Plantaginaceae) from South America - Greppi, Julian Alejandro (2017)
Mecardonia reneeae, a new species from northeastern Argentina, is described and illustrated. This taxon has certain resemblance to M. procumbens var. flagellaris, but can be easily distinguished by the combination of life form, aspect of the plant, root and stem type, sepal width, fruit size, and chromosome number (2n=4x=44). A key to distinguish it from related species is also provided